Treatment of hysterical aphonia - Bharath Raj j; Saraswathi Menon (Journal of All India Institute of Speech and Hearing, 1972)
Miss S, aged 15 years studying in VII standard reported at the Institute with acomplaint of no speech. She came to the clinic with her father, brother andbrother-in-law. She had four siblings and belonged to a middle class family. Therewas no family history of speech and hearing problems, and her development wasknown to be normal. She had developed this problem 4 days prior to coming tothe clinic